2018
DOI: 10.1371/journal.pone.0199055
|View full text |Cite
|
Sign up to set email alerts
|

Can ultrasound measures of intrinsic foot muscles and plantar soft tissues predict future diabetes-related foot disease? A systematic review

Abstract: IntroductionDiabetes mellitus (DM) is associated with hyperglycaemia and advanced glycosylation end-products. In the foot, the consequences of chronic or uncontrolled diabetes are micro and macrovascular disease, neuropathy, reduced joint mobility and structural and soft tissue changes that increase the risk of ulcer development and amputation. Diabetes foot assessment currently includes a comprehensive history, neurological and vascular assessments and examination focussed on dermatological and musculoskeleta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Measurements of plantar soft tissue thickness and assessments of plantar tissue characteristics demonstrating intra-observer reliability and agreement in this study may be useful to the diabetic population and clinicians who treat them. A number of studies have demonstrated that ultrasound measurements of the thickness of plantar soft tissues are different between people with and without diabetes, suggesting that such measurements may have a role in identifying causal or predictive changes in the feet of diabetics [ 25 ]. The measurements may also be useful in non-diabetic populations, such as those who have undergone foot reconstruction where localised high plantar pressure is suspected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Measurements of plantar soft tissue thickness and assessments of plantar tissue characteristics demonstrating intra-observer reliability and agreement in this study may be useful to the diabetic population and clinicians who treat them. A number of studies have demonstrated that ultrasound measurements of the thickness of plantar soft tissues are different between people with and without diabetes, suggesting that such measurements may have a role in identifying causal or predictive changes in the feet of diabetics [ 25 ]. The measurements may also be useful in non-diabetic populations, such as those who have undergone foot reconstruction where localised high plantar pressure is suspected.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound demonstrates this soft-tissue detail, and studies have suggested that ultrasound measurements of soft-tissue thickness [ 12 , 23 , 24 ] may have a role in assessing the risk of plantar foot ulceration in people with DM. However, the reliability of ultrasound measurements of the plantar skin and fat pad thickness are not well documented [ 25 ]. Ultrasound can also be used to depict tissue characteristics other than thickness, but such assessments are often overlooked, including those of the plantar foot in diabetic people, due to their perceived subjectivity [ 26 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, seven patients with a history of metatarsal head resection should be excluded from the analysis due to the conduct of metatarsal head resection. However, the first metatarsal was evaluated in the entire sample; this is the most reliable area for reference measurement of the plantar soft tissues [23]. Analysis of the second metatarsal could be deleted from the study due to the possible risk of statistical errors caused by the loss of data.…”
Section: Discussionmentioning
confidence: 99%
“…A generous amount of ultrasound gel was placed between the skin and the transducer to avoid compressing the skin surface. The first and second metatarsals were measured to determine the plantar soft tissue thickness, as they are considered to be more reliable metatarsal areas and have lower statistical heterogeneity [23]. The ultrasound transducer was placed perpendicularly to the sesamoid bones and the second metatarsal head, and a longitudinal section of both the sub-metatarsal skin and the fat pad was obtained to measure the first and second metatarsal heads, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…An emerging method that could be more predictive include ultrasound measurement methods that, for example, can be used in plantar soft tissues in order to predict diabetic related changes in the foot ( 232 ). In one study, it was found that Sub-MTH fat pads were significantly thinner and subhalangeal fat pads were significantly thicker in diabetic neuropathic feet compared to neuropathic controls ( 233 ).…”
Section: Cardiovascular and Other Complications In Diabetesmentioning
confidence: 99%